TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP): TEACHERS' ROLE AND THEIR CHALLENGES - Tira Nur Fitria (PRIMACY Journal of English Education and Literacy, 2023)
This study examines the role of the teacher and the challenges related to teaching English for Specific Purposes (ESP). This investigation was conducted in a library. The analysis indicates that teachers should have multiple responsibilities, such as managing/organizing learning, devising learning objectives, establishing a positive classroom environment, and evaluating student processes. The challenges that ESP teachers face in teaching ESP include the poor quality of teachers, the teachers' improper qualification and teaching methods, the absence of a theoretical framework for teaching ESP, a lack of knowledge about the field of study of their students, a lack of ESP training, the absence of a correct needs analysis, large classes, and learners with varying English proficiency levels. Students' motivation to learn English, demographic characteristics and demands of learning ESP, English proficiency, differences between languages, lack of vocabulary, reliance on the dictionary, and lack of skills in using the dictionary, especially for ESP terms. Among the environmental and other obstacles is the condition of the classroom, a lack of instructional materials, classes with an excessive number of students, and an excessive emphasis on the examination. In further research regarding curriculum and lesson plan comprehension.